2019
DOI: 10.1109/access.2019.2901957
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CAP-WDM-PON Employing Multi-Band DFT-Spread DMT Signals Based on Optical Hilbert-Transformed SSB Modulation

Abstract: We propose and experimentally demonstrate a novel carrier-less amplitude/phase modulation wavelength-division-multiplexing passive optical network (CAP-WDM-PON) with its bandwidth efficiency enhanced by using a multi-band discrete Fourier transform spread (DFT-spread) discrete multi-tone (DMT) signal based on Hilbert-transformed single-sideband (HB-SSB) modulation. The DFT-spread technique is utilized to extend orthogonal subcarriers, which effectively restrain the high-peak signal formation probability, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…M-ary quadrature amplitude modulation (M-QAM) orthogonal frequency division multiplexing (OFDM) has attracted great interest in optical wireless access networks because of its high spectrum efficiency and flexible bandwidth allocation [1][2]. As a modification of quadrature amplitude modulation OFDM (QAM-OFDM), pulse-amplitude-modulated discrete multitone (PAM-DMT) was introduced in various intensity modulated/direct detection (IM/DD) access systems such as single-mode fiber, multimode fiber, and optical wireless system to achieve real signal [3][4][5][6][7][8]. Compared with direct current (DC) biased optical OFDM (DCO-OFDM) that adds a DC bias to the original bipolar OFDM signal [9], asymmetrically clipped optical OFDM (ACO-OFDM) that only modulates the odd subcarriers [10], PAM-DMT loads information onto the imaginary (or quadrature) parts of all subcarriers.…”
Section: Introductionmentioning
confidence: 99%
“…M-ary quadrature amplitude modulation (M-QAM) orthogonal frequency division multiplexing (OFDM) has attracted great interest in optical wireless access networks because of its high spectrum efficiency and flexible bandwidth allocation [1][2]. As a modification of quadrature amplitude modulation OFDM (QAM-OFDM), pulse-amplitude-modulated discrete multitone (PAM-DMT) was introduced in various intensity modulated/direct detection (IM/DD) access systems such as single-mode fiber, multimode fiber, and optical wireless system to achieve real signal [3][4][5][6][7][8]. Compared with direct current (DC) biased optical OFDM (DCO-OFDM) that adds a DC bias to the original bipolar OFDM signal [9], asymmetrically clipped optical OFDM (ACO-OFDM) that only modulates the odd subcarriers [10], PAM-DMT loads information onto the imaginary (or quadrature) parts of all subcarriers.…”
Section: Introductionmentioning
confidence: 99%
“…This distance is even shorter for higher bandwidths as the ones needed for 50 Gb/s PAM4 based architectures. This problem can be avoided using full coherent reception or Optical Single Sideband (OSSB) modulation as proposed in [10,11], although they usually present low sensitivities. There has also been interest in the use of Krammers-Kronig receivers [12] as a mean to obtain a native Single Sideband (SSB) modulation and reception, but many of them use multicarrier modulation schemes and require a high Carrier to Signal Power Ratio (CSPR) [13].…”
Section: Introductionmentioning
confidence: 99%
“…The multi-CAP technique can reach high data rate by using different modulation formats and components with limited bandwidth and less complexity. Hence, the CAP modulation with multiband has been considered as a promising low cost solution for the multiple-user PON systems and has attracted extensive investigations [18]- [21]. In 2013, Miguel Iglesias et al experimentally demonstrated 102 Gbps transmission over 15 km fiber with 6 sub-bands multi-CAP [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Junwen Zhang et al verified a wavelength division multiplexing (WDM) CAP-PON architecture based on multi-CAP 16-QAM with 5 sub-bands [19]. In 2019, Youxu Zen et al successfully demonstrated a 6 sub-bands CAP-WDM-PON scheme with 5 wavelengths over 20 km fiber transmission based on the discrete multi-tone (DMT) and Hilbert transformed single sideband (SSB) modulation [21]. In brief, the multi-CAP technique can provide large capacity with the flexibility and elasticity of the modulation formats.…”
Section: Introductionmentioning
confidence: 99%